What is the Best Method for Assessing Lower Limb Force-Velocity Relationship? - Giroux, C.; Rabita, G.; Chollet, D.; Guilhem, G. (International Journal of Sports Medicine, 2015)
This study determined the concurrent validity and reliability of force, velocity and power measurements provided by accelerometry, linear position transducer and Samozino’s methods, during loaded squat jumps. 17 subjects performed squat jumps on 2 separate occasions in 7 loading conditions (0–60% of the maximal concentric load). Force, velocity and power patterns were averaged over the push-off phase using accelerometry, linear position transducer and a method based on key positions measurements during squat jump, and compared to force plate measurements. Concurrent validity analyses indicated very good agreement with the reference method (CV=6.4–14.5%). Force, velocity and power patterns comparison confirmed the agreement with slight differences for high-velocity movements. The validity of measurements was equivalent for all tested methods (r=0.87–0.98). Bland-Altman plots showed a lower agreement for velocity and power compared to force. Mean force, velocity and power were reliable for all methods (ICC=0.84–0.99), especially for Samozino’s method (CV=2.7–8.6%). Our findings showed that present methods are valid and reliable in different loading conditions and permit between-session comparisons and characterization of training-induced effects. While linear position transducer and accelerometer allow for examining the whole time-course of kinetic patterns, Samozino’s method benefits from a better reliability and ease of processing.
Keywords: muscle power; linear transducer; accelerometry; force plate; ballistic movements